Alzheimer Disease: Cognizance and Potential Aspect of Disease Pathophysiology & Recently Developed Therapeutic Drug Strategies - journal, Rakesh Kumar; Saini, Manita; Bhattacharya, Tilottama; Deepika, Dr; Kumari, Akancha (Journal of Drug Delivery and Therapeutics, 2024)
Alzheimer’s disease (AD) is a multifactorial neuron-degenerative old age disease which has no cure. AD causes degeneration of the neuronal cells in the brain which is the main reason of dementia, characterized by a decline in the thinking and independence in daily routine activities. In most of the cases, AD is suspected to be caused by a combination of genetic, lifestyle and environmental factors, affecting the brain over time. The currently approved therapy, which includes cholinesterase inhibitors, NMDA-receptor antagonists and their combinations provides only temporary symptomatic relief. Nowadays, the clinical research is targeting on understanding of Alzheimer pathology1. These are targeting the abnormal tau protein metabolism, removal of beta-amyloid, inflammatory response, cholinergic neuron and free radical damage treatments which can either that stop or modify the course of Alzheimer. Global efforts are continued to identify new targets to develop novel therapeutic agents for the treatment of AD. Keywords: Alzheimer disease, Dementia, Drug therapy, Drug effect, Amyloid, Amyloid precursor protein, Tau proteins, Acetyl cholinesterase enzyme